Models of defective insulin secretion in human and mouse pancreatic islets: impact of granule exocytosis, mitochondrial metabolism, and ageing - Do, HW (2015)
Type-2 diabetes (T2D), a multi-factorial disease characterised by chronic hyperglycaemia, is caused by a complex interaction between genetic and environmental factors. Genetic and phenotypic characterisations of diabetic patients suggest that a combination of β-cell failure, culminating in defective insulin secretion, as well as impairment of glucagon secretion in α-cells is central to the aetiology of the disease. Mouse models represent a valuable tool in such investigations. With the advent of large-scale genetic tools, a myriad of novel susceptibility loci associated with T2D have been identified. For many of these genes, it is unclear how genetic variation is linked to increased disease susceptibility. Our first study elucidates the implication of a transcription factor, SOX4, which is believed to underlie a T2D susceptibility locus (CDKAL1) in human. Using an N-ethyl-N-nitrosourea (ENU) mouse model, we explored β-cell function in mice carrying a point mutation in Sox4 (Sox4mt mice). This mouse strain displayed a significant reduction in glucose-stimulated insulin secretion (GSIS) that was associated with a 2-fold increase in wild-type Sox4 expression. The exocytotic events in mutant β-cells, as measured by single-vesicle (on-cell) capacitance measurements, suggested the presence of a persistent fusion pore. Subsequent failure of fusion pore expansion beyond the initial 1–2 nm results in an incomplete insulin release due to steric hindrance (insulin diameter: 3–4 nm). The proportion of full fusion events diminished in favour of kiss-and-run events in mutant β-cells. Stxbp6, which encodes amisyn, was shown to be the target gene of Sox4. Increased expression of amisyn, a protein previously shown to be involved in the stabilisation of the fusion pore in chromaffin cells, was observed in islets isolated from Sox4mt mice. The possible involvement of amisyn is further suggested by the finding that overexpression of amisyn mimicked the effect of the Sox4 mutation and resulted in reduced insulin secretion. Knockdown of amisyn expression restored the secretory defect in Sox4mt-overexpressing cells. Importantly, the effect of the Sox4 mutation was recapitulated by the overexpression of Sox4. Similar effects were obtained in the human β-cell line EndoC-βH2. We also observed a negative correlation between SOX4 expression and GSIS in a large collection of human islet preparations. There was also a positive correlation between SOX4 expression and STXBP6 (amisyn) expression and a tendency towards increased SOX4 expression in islets from organ donors with T2D. The second part of the thesis focuses on the role of the Krebs cycle enzyme fumarate hydratase (FH) in insulin release. Ablation of the Fh1 gene (which is initially implicated as a tumour suppressor in hereditary leiomyomatosis and renal cell cancer) in pancreatic β-cells led to a complete loss of GSIS, as determined by ex vivo pancreatic perfusion studies, although this was not associated with any detectable abnormalities in [Ca2+]i homeostasis, ATP production or glucose oxidation. The phenotype was rescued by the introduction of the human orthologue FH into the cytosol alone or in both the cytoplasm and mitochondria of Fh1 knockout (Fh1KO) mice, confirming the role of Fh1 in insulin secretion. Moreover, the addition of exogenous glutamate, previously implicated as a 2nd messenger between glucose metabolism and insulin secretion, corrected the insulin secretory defect in Fh1-/- β-cells. We hypothesise that the loss of GSIS in Fh1KO mice results from enhanced anaplerosis, which is necessary to replenish Krebs cycle reactants. Consequently, this is followed by the depletion of the intracellular amino acid pool (including glutamate). Thus, our study demonstrates that the pancreatic Fh1KO mouse is a novel model of severe hyperglycaemia that harbours dysregulated metabolic features at the interface between both cancer and diabetes. The final study investigates the effect of ageing, a risk factor for T2D, on glucose-stimulated insulin and glucagon release. However, GSIS increased rather than decreased with ageing in both human and mouse islets (6 and 20 mmol/l glucose). Notably, ageing was not associated with reduced insulin content. Normal calcium homeostasis was observed in old (24-month-old) mice, demonstrating that the glucose sensing machinery was intact. In human islets, the inhibitory effect of glucose on glucagon secretion deteriorated with age. In the oldest group (>60 years of age), the inhibitory effect was completely abolished with 20 mmol/l glucose, while 6 mmol/l glucose only achieved less than 20% inhibition (which was not statistically significant). Our study reports the exciting possibility that hypersecretion of glucagon represents a link between senescence and increased diabetes risk.